2006
DOI: 10.1097/01.jom.0000246229.68697.90
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Risk Among Firefighters: A Review and Meta-analysis of 32 Studies

Abstract: Our results confirm previous findings of an elevated metarelative risk for multiple myeloma among firefighters. In addition, a probable association with non-Hodgkin lymphoma, prostate, and testicular cancer was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
278
6
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 314 publications
(332 citation statements)
references
References 42 publications
21
278
6
12
Order By: Relevance
“…Their episodic intense work, combined with those health risks, contribute to myocardial infarctions being the leading cause of on duty death [9]. Healthy lifestyles are of additional importance because firefighters' risk of cancer is increased [10].…”
Section: Discussionmentioning
confidence: 99%
“…Their episodic intense work, combined with those health risks, contribute to myocardial infarctions being the leading cause of on duty death [9]. Healthy lifestyles are of additional importance because firefighters' risk of cancer is increased [10].…”
Section: Discussionmentioning
confidence: 99%
“…These results only show an overall correlation without information on the relationship between the length of work as a firefighter and the degree of risk of prostate cancer. A review by LeMasters et al (2006) supported the positive correlation between firefighting occupations and prostate cancer and reported a summary estimate risk of SRE = 1.28;95% CI:1.15-1.43 following a systematic review and meta-analyses of thirty two studies on cancer risk among firefighters. It is believed that firefighters by virtue of their occupation are susceptible to a number of cancers including multiple myeloma, non-Hodgkin's lymphoma and testicular cancer (LeMasters et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A review by LeMasters et al (2006) supported the positive correlation between firefighting occupations and prostate cancer and reported a summary estimate risk of SRE = 1.28;95% CI:1.15-1.43 following a systematic review and meta-analyses of thirty two studies on cancer risk among firefighters. It is believed that firefighters by virtue of their occupation are susceptible to a number of cancers including multiple myeloma, non-Hodgkin's lymphoma and testicular cancer (LeMasters et al, 2006). PAH (Krstev et al, 1998b) and fire smoke (Demers et al, 1994) are suspected carcinogens but the relationship has not been confirmed although believed to be plausible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations